A qualitative approach to the success factors of Universal New-Born Hearing Screening (UNHS) program in selected Malaysian Hospitals - Abdullah, Nor Azimah Chew; Ismail, Abdussalaam Iyanda; Abdul Majid, Abdul Halim; Zakaria, Mohd Normani; Hamzah, Sulaiman; Mukari, Siti Zamratol Mai Sarah (United Kingdom, 2018)
Success of UNHS models in Malaysia is indispensable, given that UNHS program plays crucial role in reducing and/or preventing hearing impairment associated with deficits in language, social, emotional, and cognitive growth of newborns, regardless of the existence of risk indicators. Against this background, the study aims to provide a profound insight and advance knowledge in the universal newborn hearing screening (UNHS) research field, the current study, using qualitative approach, examines success factors of UNHS practices in selected Malaysian Hospitals. This aspect of research is deemed imperative, given the indispensability ofsuccessful UNHS models in Malaysia. For this, open-ended interview was conducted to elicit information regarding UNHS practices from the respondents of the current study. The respondents are the matrons from Hospital Raja Perempuan Zainab 2, Kota Bahru, Kelantan, Hospital Sg, Buluh, Selangor and Hospital Taiping, Perak. Transcription of the information elicited from the interview was done manually, and the transcribed data was analyzed to determine the factors that would guarantee successful UNHS. UNHS model, which comprises of screening coverage and screening equipment, should enhance screening outcomes and reduce the cases of avoidable hearing loss. However, accomplishing successful UNHS program requires screening coverage, which is induced by knowledgeable and motivated staff, top management support, and teamwork, and adequate, movable and accessible screening equipment. Furthermore, the findings of the study highlight that UNHS program is being practiced in the selected Malaysian hospitals, but it suffers a myriad of challenges, which include dearth of staff, inadequate screening equipment, inadequate screening coverage, and difficulty in securing top management support. The overall findings of the current study accentuate that accomplishment of effective UNHS practices could require recruitment of more qualified staff, provision of more screening equipment and ensure enhanced screening coverage, as this would result to drastic reduction of the cases of avoidable hearing loss in the society. Also, the current study has contributed towards the enrichment of the relevant literature.